PENGARUH BRAND IMAGE, IKLAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE PORTAL TRAVELOKA DI KOTA DENPASAR - Ni Putu Anggi Damayanti; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
Purchasing decisions are thoughts in which individuals evaluate various choices on a product from the many choices that exist. Purchasing decisions are influenced by many factors including brand image, advertising, and price perception. This study aims to determine the effect of brand image, advertising, and price perception on purchasing decisions on the Traveloka Online Portal in Denpasar City. This research was conducted in Denpasar City in people who use the Traveloka Online Portal using a sample of 75 respondents. The sampling technique used in this research is purposive sampling technique. Data was collected through observation, interviews, questionnaires and documentation. The data analysis technique used in this research is multiple linear regression analysis which is processed using SPSS software. Based on the results of the analysis, this study shows that brand image has a positive and significant effect on purchasing decisions on the Traveloka Online Portal. Advertising has a positive and significant impact on purchasing decisions on the Traveloka Online Portal. Price perception has a positive and significant effect on purchasing decisions on the Traveloka Online Portal. Limitations in this study only focused on three variables, namely brand image, advertising and price perception and this research was only conducted on the Traveloka Online Portal.